Facile Synthesis of Novel Conducting Copolymers Based on N-Furfuryl Pyrrole and 3,4-Ethylenedioxythiophene with Enhanced Optoelectrochemical Performances Towards Electrochromic Application - Huixian Li; Xiaomeng Sun; Datai Liu; Xinchang Liu; Xianchao Du; Shuai Li; Xiaojing Xing; Xinfeng Cheng; Dongqin Bi; Dongfang Qiu (Molecules)
In this article, a series of novel conducting copolymers P(FuPy-co-EDOT) are prepared via cyclic voltammetry electropolymerization method by using N-furfuryl pyrrole (FuPy) and 3,4-ethylenedioxythiophene (EDOT) as comonomers. The molecular structure, surface morphology, electrochemical, and optical properties of the resulting copolymers are characterized in detail upon varying the feed ratios of FuPy/EDOT in the range of 1/1 to 1/9. The results demonstrate that the prepared P(FuPy-co-EDOT) copolymers with a higher proportion of EDOT units (FuPy/EDOT: 2/8~1/9) possess good redox activity, tunable optical absorption performances, and low band gaps (1.75~1.86 eV). Spectroelectrochemistry studies indicate that the resulting copolymers with increased EDOT units show strengthened electrochromic characteristics, exhibiting a red-to-green-to-blue multicolor reversible transition, especially for the P(FuPy1-co-EDOT9) copolymer films. They also show increased optical contrast (9~34%), fast response time (0.8~2.4 s), and good coloring efficiency (110~362 cm2 C−1). Additionally, the complementary bilayer P(FuPy-co-EDOT)/PEDOT electrochromic devices (ECDs) are also assembled and evaluated to hold excellent electrochromic switching performances with relatively high optical contrast (25%), rapid response time (0.9 s), and satisfactory coloring efficiency (416 cm2 C−1). Together with the superior open circuit memory and cycling stability, they can be used as a new type of electrochromic material and have considerable prospects as promising candidates for electrochromic devices.